2019
DOI: 10.24171/j.phrp.2019.10.5.02
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Complex Intervention Program for Unilateral Neglect in Patients with Acute-Phase Stroke: A Randomized Controlled Trial

Abstract: ObjectivesThe purpose of this study was to examine the combined effects of Prism Adaptation (PA) plus functional electrical stimulation (FES) on stroke patients with unilateral neglect, and suggest a new intervention method for acute-phase stroke patients.MethodsThere were 30 patients included in this study from April to October 2016 that had unilateral neglect whilst hospitalized following a stroke (diagnosed by a professional). The participants, who were patients receiving occupational therapy, understood th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…In contrast, although previous studies have explored PA in combination with other treatments, most studies have selected therapies with the same bottom-up approach ( 19 , 20 , 48 ). It is notable that the two interventions chosen for the present study stem from the following two different approaches: the “top-down” approach aims to improve perceptual and behavioral biases by acting on disrupted consciousness and thus on higher-level cognitive processes, and the “bottom-up” approach is a physiological approach that aims to influence sensory-motor levels through passive sensory manipulation or visuomotor adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, although previous studies have explored PA in combination with other treatments, most studies have selected therapies with the same bottom-up approach ( 19 , 20 , 48 ). It is notable that the two interventions chosen for the present study stem from the following two different approaches: the “top-down” approach aims to improve perceptual and behavioral biases by acting on disrupted consciousness and thus on higher-level cognitive processes, and the “bottom-up” approach is a physiological approach that aims to influence sensory-motor levels through passive sensory manipulation or visuomotor adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we speculate that combining PA with one approach will yield better results. In previous studies, Saevarsson et al ( 19 ) and Choi et al ( 20 ) combined PA with neck vibration and functional electrical stimulation, respectively, and both showed that the combined intervention better improved USN symptoms. However, the combination of these two studies only increased the number of interventions without mentioning the possible theoretical basis.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study of 12 stroke patients with unilateral neglect found that a combination therapy with 20 min of PA and NV produced more synergistic intervention effects compared to that of NV alone [ 16 ]. In another study conducted on 30 patients of acute stroke with unilateral neglect, the combined effects of PA and FES were greater than the effects of either intervention alone [ 20 ]. In a study that applied a complex intervention, which combined an eye patch and optokinetic stimulation, positive effects were shown in terms of the reduction in unilateral neglect and improved ADL, compared to the control [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the effects of only visual scanning stimulation (VSC), the combination of VSC with transcutaneous electrical nerve stimulation (TENS) exerted greater positive effects for reducing unilateral neglect [ 19 ]. Similarly, compared to the use of either PA or functional electrical stimulation (FES), the combination of PA and FES conferred greater positive effects for symptom reduction [ 20 ]. However, these previous studies were mostly conducted on acute stroke patients, and this limitation hindered the verification of whether the improvement in unilateral neglect was owed to the treatment or whether it was attributable to spontaneous recovery.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the meta-analysis included studies in which the control group received a non-standard treatment intervention, for example, functional electrical stimulation (Choi et al, 2019). Therefore, the overall effect size estimate is not an absolute comparison of prism adaptation to treatment as usual.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%